PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Wulan Fitriani; Yuyu Yuliati; Indani Damayanti (STKIP Subang, 2025)
This study was motivated by the insufficient science literacy skills of fifth-grade students at SDN Talaga Wetan III and SDN Banjaran. The purpose of this study was to determine the effect of the Problem-Based Learning (PBL) model on students' science literacy skills. The research method used was a quasi-experimental design with a non-equivalent pre-test and post-test control group design. This study was conducted in fifth grade elementary school during the 2025/2026 academic year with 25 students in the experimental class and 25 students in the control class as research subjects. The experimental class was given the Problem-Based Learning (PBL) model, while the control class was given the Direct Instruction model. Both groups were given pre-tests and post-tests using the same test instruments. The pre-test and post-test data were analyzed using SPSS Version 27. The results of the data analysis showed that the science literacy skills of the experimental class improved more significantly than those of the control class, which remained low. Thus, it can be concluded that there is a difference and influence of the Problem-Based Learning (PBL) model in the fifth grade of SDN Talaga Wetan III and SDN Banjaran. The implication for students is that the PBL learning model effectively enhances their science literacy skills during the learning process.